Temperature analysis in friction stir welding of ADC12/5052 dissimilar aluminum alloys - KATO, Hajime; KANEUCHI, Takao; KOKUBO, Masafumi; TAKAYAMA, Yoshimasa; KAZUI, Shinichi; HIRANO, Satoshi (Journal of Japan Institute of Light Metals, 2007)
Temperature analysis has been performed in friction stir welding (FSW) of ADC12 and A5052 dissimilar aluminum alloys. The temperature at the stir zone and four points on each side of the joint line was measured during FSW in various conditions. In addition, an analytical model assumed that the work generated by the rotation of the tool led to the work for stirring materials and heat generation of the material and the tool. The temperature of the stir zone (SZ) where A5052 were FSWed was about 30 K higher than that of ADC12. The temperature of SZ of the advancing side (AS) : A5052/the retreating side (RS) : ADC12 was about 30 K higher than that of AS : ADC12/RS : A5052. The flow stress of the materials in FSW was calculated based on the temperature obtained in the experiment. The analytical model could predict appropriately that the motor power consisted of the heat generated by friction and the work generated by the rotation of the tool.